Determinan Matriks Persegi Panjang - Ryan Eka Putra; Yusmet Rizal (Journal of Mathematics UNP, 2020)
Abstract —One study in matrix theory is determinant. Matrix determinants are usually used to find the inverse of a matrix, to solve a system of linear equations, and determine the characteristic equations of a problem in determining eigenvalues. The concept that developed so far is to determine the determinant of the matrix only focused on a square matrix. The next problem is what if the matrix is not a square matrix. However ,there is a method developed by Radic to find the determinant value of a rectangular matrix. This research is a theoretical research with literature study. The purpose of this research is to determine the concept of determinant rectangular matrix. The concept that will be discussed in this research is how to calculate the determinants of a rectangular matrix and how the properties of a rectangular matrix determinant. The results of determinant rectangular matrix is an extension of the definition of the determinant which shows the series of determinants of sub matrix for a square matrix. Keywords — Determinant, Matrix, Radic Method.